A Vision toward Ultimate Optical Out‐Coupling for Organic Light‐Emitting Diode Displays: 3D Pixel Configuration. Issue 10 (29th August 2018) - Chen, Yi‐Jiun; Lee, Wei‐Kai; Chen, Yi‐Ting; Lin, Chun‐Yu; Wen, Sheng‐Wen; Jiao, Min; Su, Guo‐Dong; Lin, Hoang Yan; Visser, Robert J.; Kwak, Byungsung Leo; Chen, Chung‐Chia; Lin, Wan‐Yu; et al.
Abstract: Despite stringent power consumption requirements in many applications, over years organic light‐emitting diode (OLED) displays still suffer unsatisfactory energy efficiency due to poor light extraction. Approaches have been reported for OLED light out‐coupling, but they in general are not applicable for OLED displays due to difficulties in display image quality and fabrication complexity and compatibility. Thus to date, an effective and feasible light extraction technique that can boost efficiencies and yet keep image quality is still lacking and remains a great challenge. Here, a highly effective and scalable extraction‐enhancing OLED display pixel structure is proposed based on embedding the OLED inside a three‐dimensional reflective concave structure covered with a patterned high‐index filler. It can couple as much internal emission as possible into the filler region and then redirect otherwise confined light for out‐coupling. Comprehensive multi‐scale optical simulation validates that ultimately high light extraction efficiency approaching ≈80% and excellent viewing characteristics are simultaneously achievable with optimized structures using highly transparent top electrodes. This scheme is scalable and wavelength insensitive, and generally applicable to all red, green, and blue pixels in high‐resolution full‐color displays. Results of this work are believed to shed light on the development of future generations of advanced OLED displays. Abstract : A highly effective and scalable light‐extraction pixel structure, based on embedding an organic light‐emitting diode (OLED) inside a 3D reflective concave structure and patterned high‐index filler coverage, is reported for OLED displays. Comprehensive multiscale optical simulation indicates that ultimately high light extraction efficiency approaching 80% and excellent viewing characteristics are simultaneously achievable with optimized structures using highly transparent top electrodes.